Effect of Earnings Per Shares on Capital Structure Choice of Listed Non-Financial Firms in Nigeria - Olanrewaju Isola Fatoki; Tobias Olweny (European Scientific Journal, ESJ, 2017)
The main objective of this paper is to examine the effect of financial performance on capital structure of listed non-financial firms in Nigeria. This was guided by assessing the earnings per share on capital structure choice. The causal research design was adopted while a total of 87 samples was included in the study. The estimated results are statistically significant at all levels of Capital Structure. Based on the significance of these results it was concluded that both the efficiency risk and franchise value hypotheses of the reverse causality hypothesis are observable in the capital structure choice of the firms.